2008
DOI: 10.1080/14631370802444575
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy stabilisation, changes in the banking system and interest rate pass-through: the Czech Republic 1999–2006

Abstract: This article deals with the relationship between market and client interest rates in the period of inflation stabilisation and banking system transformation in the Czech Republic in 1999–2006. It analyses the character of short-run and long-run equilibrium of the transmission of market interest rates to lending and deposit interest rates. In the theoretical part crucial characteristics of the banking system in transition countries and their effects on interest rate dynamics are discussed. These are the strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The degree of pass-through is stronger on the deposit rate compared to the lending rate. This finding is consistent with the observation of Bruna (2008) who pointed out that deposit rate reacts quicker than the lending rate to the change of the money market rate. The work of Tai et al (2012) and Tang et al (2015) also reported that the deposit rate has a higher degree of pass-through than the lending rate.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The degree of pass-through is stronger on the deposit rate compared to the lending rate. This finding is consistent with the observation of Bruna (2008) who pointed out that deposit rate reacts quicker than the lending rate to the change of the money market rate. The work of Tai et al (2012) and Tang et al (2015) also reported that the deposit rate has a higher degree of pass-through than the lending rate.…”
Section: Resultssupporting
confidence: 82%
“…Bruna (2008) claimed that changes in the market interest rate tended to have a different impact on the adjustment of lending and deposit rates regardless of the term. In tandem with this, Tai et al (2012) illustrated that the deposit rate was found to have a slightly higher pass-through effect compared to the lending rate in Asia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the cointegration and error correction analysis revealed that there are still higher passthrough between policy rate and some corporate lending rates. Bruna (2008) investigated the effect of market interest rates on lending and deposit interest rate in Czech Republic alone during inflation stabilization period 1999-2006. The results of cointegration analysis suggested that lending and deposit rates react differently to changes in market interest rates both in long run and in short run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Important influence of banking competition on the economy has been emphasized in both theoretical and economic policy literature. Banking competition impacts the interest rate pass-through as in more competitive markets bank interest rates respond more strongly to the changes in market rates (see Bikker et al 2011, Bruna, 2008. The issues also widely discussed in the literature are whether the banking competition improves or reduces stability of financial system (see e.g.…”
Section: Introductionmentioning
confidence: 99%